"Outside The Framed Image":1 An Empirical Perspective On/From The Story Of FÉlix Diallo And His Archive. Issue 2 (4th May 2018) - Nimis, Érika
Abstract : This article focuses on recovering the partly destroyed archive of Malian photographer Félix Diallo (1931–1997), who was active between the mid-1950s and the mid-1980s in Kita, a small town in rural southwestern Mali. Revisiting fieldwork that was initiated 20 years ago, this article presents an empirical and chronological analysis of Félix Diallo's career as the first commercial photographer in Kita and explains his archive's preservation and valorization through digitization, which led to an exhibition organized in March 2018 in his hometown. Within an overview of his career and legacy, it questions the ways in which the history of Malian photography has, for the past 25 years, primarily centered on the art market's interests.